Human rights shaming and FDI: effects of the UN Human Rights Commission and Council - Vadlamannati, Krishna Chaitanya; Janz, Nicole; Berntsen, Øyvind Isachsen (Elsevier, 2018)
Do public condemnations by the United Nations human rights bodies lead to foreign direct investment (FDI) loss for abusive regimes? The Human Rights Commission and later Council (UNHRCC) are internationally legitimized tools where member states shame repressive regimes for human rights violations in public resolutions. We argue that these resolutions can influence foreign investors in two main ways: (1) They signal that a state is an outcast, unable to secure alliances within the UN human rights bodies that protect it from being publicly shamed, with negative consequences for investment attractiveness (‘outcast’ effect). (2) They signal that a state is one of the most rogue, severe human rights violators because voting members of the UNHRCC may be aware of many human rights violations, but they pass resolutions only in the harshest cases (‘bottleneck’ effect). Any MNC associated with such a country risks severe reputational damage. Results from a panel data analysis of 165 countries (1977–2013) confirm that UNHRCC condemnations deter FDI. This effect is amplified by media reporting of human rights abuse, and stronger and more robust than a bad human rights record of a state itself. NGO shaming and milder UNHRCC sanctions (which do not reach resolution stage) have less strong effects, although the result on NGO shaming is to be seen with caution due to a reduced sample size.